Mangrove Ecotourism Management and Development Strategy in Tanjung Limau Village, Muara Badak District - Ismail Ismail; Helminuddin .; Abdunnur . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
From the results of the study it can be concluded that mangrove ecosystems in the village of Tanjung Limau, Muara Badak District, were found in 5 types, namely (R. apiculata, A. alba, N. fruticans, C. tagal and S. alba). With species density ranging from 1-68 individuals / ha and thickness of mangroves between 160-200 m. While the results of the tourism suitability index obtained categories according to the carrying capacity of the region 8-10 people / day. There are 3 management strategies and development of mangrove ecotourism in Tanjung Limau Village, namely: first to make proposals to the private sector and the government in improving the management and development of mangrove ecotourism through capital assistance and improvement of tourism facilities and infrastructure in Tanjung Village, secondly to increase / encourage government participation in helping the community to manage and develop mangrove ecotourism and thirdly to coordinate and collaborate between communities, NGOs, the private sector and the government in managing and developing mangrove ecotourism.